2004
DOI: 10.1093/aje/kwh073
|View full text |Cite
|
Sign up to set email alerts
|

Episodic Alcohol Use and Risk of Nonfatal Injury

Abstract: Usual and acute alcohol consumption are important risk factors for injury. Although alcohol-dependent people are thought to be at increased risk of injury, there are few reports suggesting that their risk is greater than that of nondependent alcohol users in a given episode of alcohol use. The authors conducted a case-crossover analysis of data on 705 injury patients from a hospital emergency department in Mexico City, Mexico, collected in 2002. The majority of the sample was male (60%) and over 30 years old (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 23 publications
6
52
1
1
Order By: Relevance
“…Differen--tial recall may lead to an overestimate of the association between alcohol and injury if patients are more likely to remember and report alcohol use in the short term. Prior case-crossover research on alcohol consumption and injury has used other control periods, [1][2][3][4] ranging from a day to a year, suggesting that the findings reported here are robust. Legal or other issues, however, may encour--age patients to minimize their reports of drinking prior to an injury, for ex--ample, if they were involved in a traffic accident.…”
Section: Study Limitationsmentioning
confidence: 53%
See 3 more Smart Citations
“…Differen--tial recall may lead to an overestimate of the association between alcohol and injury if patients are more likely to remember and report alcohol use in the short term. Prior case-crossover research on alcohol consumption and injury has used other control periods, [1][2][3][4] ranging from a day to a year, suggesting that the findings reported here are robust. Legal or other issues, however, may encour--age patients to minimize their reports of drinking prior to an injury, for ex--ample, if they were involved in a traffic accident.…”
Section: Study Limitationsmentioning
confidence: 53%
“…Following the method used in a prior report 4 we matched responses from two In some cases data do not add up to 4320 either because data were missing for whether alcohol was consumed 6 hours before the injury or due to weighting and rounding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hospital based study in Mexico City found the estimated relative risk of injury for patients who reported having consumed alcohol within 6 hours prior to injury was 3.97 (95% CI: 2.88, 5.48). 24 This increase in the relative risk was concentrated within the first 2 hours after drinking; there was a positive association of increasing risk with increasing number of drinks consumed. However, our study did not measure any alcohol drinks and related to injury.…”
mentioning
confidence: 92%